The Decline of Islamic Local Authority and the Dilemma of Islamic Aboge Community in Central Java - Muhtada, Dani (Islamic Studies Review, 2023)
The Aboge Islamic community in Onje Purbalingga has been one of the most prominent Aboge communities in Central Java. Every year, this community is the subject of media attention due to its different method for determining the beginning of the months of Ramadan and Shawwal. In Onje, the Aboge used to be the majority. Everyone in the village started their fasting for Ramadan and celebrated their Eid based on the Islamic Aboge calendar. The Aboge imam previously had significant influence on religious and socio-cultural life in the community. However, this influence is waning. The Aboge are no longer the majority in the village. This paper provides an analysis on why Aboge Imams started to lose their religious authority in the community. Why did some members of the community adhere to Aboge Islamic traditions while others did not? Using an ethnographic method, this paper argues that the decline of Aboge leaders' influence is shaped not only by the challenges of modernity, but also a process of bureaucratizing sharī‘ah as well as the weak institution of the local Aboge community.